Traditionally used anti-diabetic plants in Kathua district of Union Territory of Jammu and Kashmir, India. - Parasher, Madhvi; Pandey, Devendra Kumar; Manhas, R.K. (Journal of Ethnopharmacology)
[Display omitted] • The manuscript reports the anti-diabetic plants used by the locals, Gujjar tribe, and traditional health practitioners of Kathua district. • This is first such study from Union Territory of Jammu and Kashmir, India. • A total of 310 informants comprising of 16 THPs (01 female and 15 males), 93 tribe informants (19 females and 74 males), and 201 local ethnic Dogras (88 females and 113 males) participated in the present study. • A total of 63 species from 34 families and 58 genera were reported by the informants. • The most used life forms were herbs with 47.6% contribution whereas Leaves (40%) were the most used plant parts. • The most important anti-diabetic plants of Kathua district (Table 2) were Berberis lyceum Royle (UR, 83; RFC, 0.24), Syzygium cumini (L.) Skeels. (67; 22), and Trigonella-foenum-graceum L. (90; 0.18). • The highest consensus for sharing of the diabetic knowledge was reported for locals. • Pharmacological validation of species like Artemisia scoparia Waldst. & Kit., Pilea scripta (Buch.-Ham. ex D. Don) Wedd., Rhabdosia rugosa Wall. ex. Benth, Saussurea lappa (Decne.) C. B. Clarke, and Skimmia anquetilia N.P. Taylor & Airy Shaw, Bergenia ciliata (Haw.) Sternb., and Coccinia indica Wight & Arn., were lacking • Pilea scripta (Buch.-Ham. ex D. Don) Wedd., Rhabdosia rugosa Wall.ex. Benth, and Skimmia anquetilia N.P. Taylor & Airy Shaw are new addition to the list of anti-diabetic plants.